ytotoxic effect of n-hexane insoluble fraction obtained from kloroform extract of kembang bulan leaves [Tithonia diversifolia (Hemsley) A. Gray] on HeLa cells and mechanism detection by Hoechst 33342 - Zany sari Vindawati, Rita Rakhmawati, Mae S.H Wahyuningsih, Rul Afiyah Syarif, (Universitas Gadjah Mada, 2007)
Background: Tithonia diversifolia (Hemsley) A.Gray is a plant traditionally used to cure various diseases. The previous study indicated that n-hexane insoluble fraction of chloroform extract of T. diversifolias leaves showed cytotoxic effect on Hela cells. Separation of n-hexane insoluble fraction into several fractions was conducted in order to simplify the components. Therefore, compounds responsible for cytotoxiceffect and their mechanism of action can be determined. .Objectives: To determine fraction having the most cytotoxic effect and its mechanism of action obtained from n-hexane insoluble fractions of T.diversifolia leaves on Hela cells.Materials and methods: Fractionation of n-hexane insoluble fraction from chloroform extract of T. diversifolia leaves was done by using vacuum liquid chromatography. By MTT assay, the cytotoxic effect of fractions on Hela cells in vitro was determined. and doxorubicin was used as positive control. Each group was tested for 3 times In = 3) and the growth inhibition percentage of Hela cells was counted. The data was analyzed by probit regression, and mechanism of action of the active fraction is conducted by staining with hoechst 33342.Results: Fractionation gave five fractions IF1-5). The ICso levels obtained of those fractions were : F1 having ICso = 32.168 :!: 12.513; F2 = 11.416 :!: 0.535; F3 III = 6.223 :!: 1.303; F4 = 94.308 :!: 7.843; and F5 = 41.740 :!: 6.381Ig/ml; while the ICso value of doxorubicin was 0.241 :!: 0.170 Iglml. Conclusions: Fraction 3 of the n-hexane insoluble displayed the highest cytotoxic effect on Hela cells with ICso= 6.223:!:: 1.303 Iglml. Fraction 3 at the concentration of 3.93 uglml caused chromatin condensation and fragmentation of DNA on Hela cells.Key words: T. diversifolia, cytotoxic effect. Hela cells, insoluble n-hexane fractions